Effects of white rice-based carbohydrates diets on body weight and metabolic parameters in rats - Osman, Nur Maziah Hanum; Mohd Yusof, Barakatun Nisak; Jeevetha, Subramaniam; Ismail, Amin; Azlan, Azrina; Goh, Yong Meng; Kamaruddin, Nor Azmi; Wakisaka, Minato (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: We clarified the extent to which white rice (WR)-based carbohydrate diets affect body weight and metabolic parameters in rats. Methods: In this experimental study, a male Sprague Dawley (n=32) rats fed with WRbased CHO diet in two different proportions of total energy intake (TEI 55% moderate-CHO (MCHO, n=8) and 65% High-CHO (HCHO, n=8)) or high-fat diet (HFD, n=8) were compared with rats maintained on standard pellet diet (SD, n=8) for eight weeks period. Carbohydrate sources in the HFD and SD were mainly based on cornstarch (25% of amylose). Outcomes measures include body weight and metabolic parameters. Results: At baseline, body weight and metabolic parameters (fasting plasma glucose, insulin, and triglyceride levels) were comparable in all rats. Despite higher daily caloric intake in rats fed with HFD (103.9±3.0) than the other diets, no significant differences in body weight between groups after 8 weeks of study. However, rats’ feds with WR-based CHO diets (both moderate and high carbohydrates) had higher fasting blood glucose (MCHO=12.8±1.6, HCHO=16.9±2.4) and triglycerides level (MCHO=1.2±0.0, HCHO=1.3±0.0) than rats in cornstarch-based HFD and SD (p <0.05). Both HFD and HCHO had higher fasting insulin than MCHO and SD (p<0.05), but the homeostatic model assessment of insulin resistance (HOMA-IR) was significantly higher in WR-based CHO diets (both moderate and high carbohydrates) than the rats in cornstarch-based HFD and SD (p<0.05). Conclusion: A WR-based CHO diet exhibits higher fasting blood glucose, triglycerides, and insulin resistance state than a high-fat diet without a significant impact on body weight. These findings may explain the growing incidence of diabetes in Asia and worth studying further.